Klasifikasi Penyakit Jantung Menggunakan Extreme Gradient Boosting - Fernando, Gillang; Mimtazulfaqhi Zaydan, Haekal; Akbar, Iqmal; Dwi Irawan, Ryan (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
Heart disease or cardiovascular disease is a condition that causes restriction and blockage of blood vessels, which is one of the most deadly diseases in all countries. Risk of disease Heart disease is an event that cannot be avoided due to lack of attention to heart health. implementing a healthy lifestyle and healthy diet. This requires a heart disease risk analysis. Explanation is one of the methods widely used to extract data to determine predictable decisions. based on previous data processed by translation algorithms.